(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2026)
This article presents the results of research on drip irrigation of intensive orchards in order to increase the yield of high-quality crops from repeated crops and improve the land reclamation conditions under water shortage conditions. The results of experiments conducted to study the effect of irrigation regimes on the yield of the Golden Devishes variety of intensively planted apple trees in the conditions of repeated alluvial soils of the Bukhara region with a groundwater level of 1.5–2.0 meters are presented.